2002
DOI: 10.1046/j.1439-0507.2002.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumour necrosis factor‐α (TNF‐α) and platelet‐activating factor (PAF) interaction on murine candidosis

Abstract: Tumour necrosis factor-alpha (TNF-alpha) is related to some other factors in addition to being the essential cytokine of the sepsis which results from Candida infections. In our study, we investigated serum TNF-alpha levels, measured by enzyme-linked immunosorbent assay (ELISA), and platelet-activating factor (PAF)-like activity, measured by high-pressure liquid chromatography (HPLC) of the mice infected with Candida species. The PAF antagonist, ginkgolide BN 52021 was used to evaluate the possible interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…With C. albicans , TNF‐α gene activation peaked at 2 and 4 h after contact, followed by a 50% reduction at 8 h, then another peak at 24 h. This biphasic response with C. albicans may be explained by the fact that, at early contact periods, the gene is highly activated and the TNF‐α mRNA has to be translated into protein before a new cycle of gene activation begins. Although there was a significant difference in experimental design, our results are in agreement with those of Kalkanci et al . (2002), who reported increased levels of TNF‐α in mice infected with C. albicans .…”
Section: Discussionsupporting
confidence: 93%
“…With C. albicans , TNF‐α gene activation peaked at 2 and 4 h after contact, followed by a 50% reduction at 8 h, then another peak at 24 h. This biphasic response with C. albicans may be explained by the fact that, at early contact periods, the gene is highly activated and the TNF‐α mRNA has to be translated into protein before a new cycle of gene activation begins. Although there was a significant difference in experimental design, our results are in agreement with those of Kalkanci et al . (2002), who reported increased levels of TNF‐α in mice infected with C. albicans .…”
Section: Discussionsupporting
confidence: 93%
“…TNF- α also can reduce the amount of nitrate in normal sperm and affects NO synthesis, which is necessary for sperm movement [13]. Studies have reported that PAF and TNF- α can mutually cooperate with each other to promote the progress of inflammatory response [14], such as acute lung injury [15], monilia infection [16], and necrotizing enterocolitis [17]. How is the PAF expression in the condition of reproductive tract infection?…”
Section: Discussionmentioning
confidence: 99%